(untitled) (Annals of Medical Research, 2021)
Psoriasis is a common multisystem inflammatory chronic disease with predominantly skin and joint manifestations manifesting with remissions and exacerbations. It is a common skin disorder characterized by focal formation of raised plaques that constantly shed scales derived from excessive growth of skin epithelial cells. It is believed to be genetically linked but can also be triggered by mechanical, ultraviolet and chemical injury, various infections, drugs, psychological stress, and smoking. Oral manifestations of psoriasis are rare and are often difficult to diagnose. Oral psoriasis is a rare entity and geographic tongue is significantly more frequent in psoriatic patients but only a limited data is available so psoriatic patients should be encouraged to undergo routine dental checkups.